Tephrostratigraphy Study Using Petrographic Method in Leles Sub-basin, Bogor, WestJava - Carrisa, Dea; Nasir, Muhammad; Sendjaja, Yoga Andriana; Ilmi, Nisa Nurul; Sunardi, Edy (Faculty of Geological Engineering, Universitas Padjadjaran, 2017)
Tephrostratigraphy is a study used in determining pyroclastics layers,especially those in Ash/Tephrograin-sized, that can be used as a correlational tool to find out the order of sedimentation from one volcanic eruption. Leles Sub-Basinal, Garut, is composed mainly by Quartenary Sediment on the toppest layer and Tertiary Sediment on the bottom (Sunardi,2014). These thing of Garut Basin located in a plateau which is surrounded by volcanic plateau and dominated by lake sediment, and geographically located at low latitudes (Sunardi,2016). Based on the existence of Leles Sub-Basinal which is located on active volcanic complex, followed by its pyroclatics sediments, it is very ideal for this area to be the object of Tephrostratigraphy Study. Moreover, earlier study was never been done before thoroughly at LelesSub-Basinal area.Based on mineralogical study, the tephroof Leles Sub-Basinal divided to Crystal Tuf, Lithic Tuf,and Vitric Tuf (Schmidt,1981). The commonly found minerals are quartz, plagioclase, pyroxen, feldspar, and opaque.The emersion of other minerals, suchasolivin, amphibole, and biotite are not visible in general. Based on the presentastion of that main minerals, it was concluded that the tephrolocated in Leles Sub-Basinal came fromandesitic and basaltic magma types. While from granulometric analysis, tephro from Leles Sub-Basinal was grouped in coarse ash and fine ash with well sorting and fall deposits mechanism of sedimentation. This tephrocontains many heavy minerals with bulk density variated around 2850-2900 kg/m3, which consists of apatite, biotite, and hornblende. Those heavy minerals are commonly found in ash falls lithology (Gale & Hoare, 2011). Stratigraphically, there were two period so feruption happening at Leles Sub-Basinal area, with unidentified volcanic vents due to lack of data. It is also concluded that the supported station in the south has stratigraphical relationship with keystation. Keywords: Tephro, Tephrostratigraphy, Tuf, Leles Sub-Basinal.